EFFECTIVENESS OF GROUP CONCELING WITH TECHNIQUES ASSERTIVE TRAINING TO IMPROVE CONFIDENCE IN STUDENTS IN SMP NEGERI 2 SONGGON - Wicaksono Hariberthus (SOSIOEDUKASI, 2020)
This study aimed to obtain the implementation of group counseling and self-confidence condition students with the application of group counseling withtechniques assertive training for increase the confidence of junior high school students, and know the effectiveness of the implementation of group counseling withtechniques assertive training to increase student confidence. This research is an experimental research that is a way to find a causal relationship between two factors that are intentionally caused by researchers by reducing other factors that can interfere. The results showed that the group counseling model withtechniques assertive training proved effective in increasing student confidence. This is indicated by the test results from the calculation of the confidence scale on the total score of students before being given a treatment (pre test) and after being given a treatment (post test) obtained a probability value below 0.05 (0.006 <0.05). It is recommended to the guidance and counseling teacher to always improve their competence as a BK practitioner, and the group counseling model withtechniques assertive training can be used as a service model in helping to increase the confidence of middle school students.